Creativity Differentiation Values In the Holy Quran - Al-Hiti, Omar Abdul SattarRukan (International Journal of Psychosocial Rehabilitation, 2020)
We are in an age in which many Muslims deviate severely from the correct belief in worship, work, and behavior, and some concepts have changed, such as the concept of there is no god but God, as it turned into a word spoken by the tongue. This does not exist in the real world; rather, it is one of the misconceptions that our generation followed. Today man looked at his fellow man when he was dominated by the spirit of fanaticism and arrogance, so he considered color or gender as a basis for differentiation and distinction, and when this opinion is wrong and those foundations are invalid, and these standards are corrupt, Islam came to smash the false human scale, eliminate its corrupt standards, and deny artificial standards, And it came to achieve fairness, it came to lay the solid foundation upon which humans make a difference, and here the Qur’an directs attention to this divine.